Recent Results from the SAFIR Project - M. Sánchez-Portal; M. Castillo-Fraile; C. Ramos Almeida; P. Esquej; A. Alonso-Herrero; A. M. Pérez García; J. Acosta-Pulido; B. Altieri; A. Bongiovanni; J. M. Castro Céron; J. Cepa; D. Coia; et al. (Acta Polytechnica CTU Proceedings)
The "Seyfert and star formation Activity in the Far-Infrared" (SAFIR) project is aimed at studying the physical nature of the nuclear IR emission and star formation properties of a small sample of nearby Seyfert galaxies observed with the PACS and SPIRE instruments on board the Herschel space observatory. In this paper, we review the achieved results, that reveal the importance of the far-IR range to improve the quality and reliability of the estimates of basic AGN torus parameters, and describe some preliminary outcome from the on-going work on the dust properties of resolved AGN host galaxies.